Analysis of Project Manager’s Role in Organizing Elementary and Junior High School Spelling Bee Competition at Polbeng Business Expo Chapter II - Nuri Darmawan; Yanisha Dwi Astari (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the role of Project Managers in organizing Spelling Bee competitions for elementary and junior high school students held at Polbeng Business Expo Chapter II. The objective of this study are to determine the role of Project Managers, the challenges faced during the competition, and the solutions implemented to overcome the obstacles that arose. This study uses a qualitative approach with data collection techniques through in-depth interviews and observation. The collected data was the analyzed using thematic analysis to identify the roles, challenges, and solutions implemented by the Project Manager covers four main aspects: first, developing a project plan that include a schedule, task allocation, and resources needed for the smooth running of the event. Second, monitoring project progress reguraly through weekly evaluations and schedule adjustments when necessary. Third, ensuring effective communication between all relevant parties, both internal teams and external parties such as participants and judges. Fourth, developing media strategies to promote the event to reach a wider audience. The challenges faced included participants delays, ineffective team coordination, and unexpected technical problems. Solutions provides to overcome these challenges include developing contingency plans, clear task distribution, and regular evaluations to ensure the smooth running of the event. This study provides in-depth insight into the importance of the Project Manager’s role in managing events and provides solutions to various obstacles encountered, as well as recommending the implementation of better project management for similar event in the future.